OPTIMALISASI IMPLEMENTASI BUMDES JAYA LESTARI DESA SUNGIKULON, KABUPATEN PASURUAN: ANALISIS STRATEGI, KENDALA, DAN KONTRIBUSI TERHADAP PENDAPATAN ASLI DESA - Ahmad Yusroni; Andra Pratama Juliyanto; Yuyun Eka Kartika Sari; Muhammad Khairul Anwar; Nabila Septia Rosa (Program Studi Ilmu Administrasi Negara, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Timor, 2025)
This study aims to analyze the implementation of BUMDes Jaya Lestari in Sungikulon Village by focusing on management optimization strategies, existing constraints, and its contribution to Village Own-Source Revenue (PADes). A qualitative single-case study design was employed using in-depth interviews, participatory observation of business units such as Pospay services and 3-kg LPG outlets, and document analysis of financial statements, sales logbooks, and other operational records. Data were analyzed through an interactive process involving data reduction, data display, and conclusion drawing. The findings indicate that strategies related to human resource capacity building, product promotion, partnerships with PT. Pos and PT. Pertamina, and capital strengthening are only sufficient to maintain operational continuity and have not yet generated a significant contribution to PADes. Internal constraints include limited managerial and financial skills, low transparency, and less effective leadership, while external constraints arise from market competition and low community participation. The contribution of BUMDes is more evident in non-financial aspects such as service facilitation, economic empowerment, and social impact, whereas its direct financial contribution to PADes remains very limited.